A fossil sea turtle (Testudines: Pan-Cheloniidae) from the upper Oligocene Pomahaka Formation, New Zealand. Issue 1 (2nd January 2017) - Gard, Henry J.L.; Fordyce, R. Ewan
Abstract : Gard, H.J.L. & Fordyce, R.E., August 2016. A fossil sea turtle (Testudines: Pan-Cheloniidae) from the upper Oligocene Pomahaka Formation, New Zealand. Alcheringa 41, XX–XX. ISSN 0311-5518. An isolated turtle xiphiplastron similar to that of Puppigerus sp. is described from the upper Oligocene (27.3–25.2 Ma) Pomahaka Formation near Tapanui, Otago, New Zealand. The bone is unlike any previously described turtle from the Cenozoic of New Zealand and is from a newly recognized estuarine vertebrate locality. It represents the first Oligocene cheloniid turtle bone described from the southwest Pacific. Henry J. L. Gard [ henrygard@hotmail.com ] and R. Ewan Fordyce, [ ewan.fordyce@otago.ac.nz ], Department of Geology, University of Otago, PO Box 56, Dunedin, 9054, Otago, New Zealand .